Preliminary Validation of Aerosol Retrievals from Aeolus Satellite Mission Based on Ground-Based Lidar Measurements in the Iberian Peninsula - Abril-Gago, Jesus (2022)
This work reports the validation of the Aeolus L2A products (particle backscatter profile at 355 nm) from 22th August 2018 (satellite launch) to 31st May 2020.